The implications of condominium neighbourhoods for long-term urban revitalisation. (January 2017) - Webb, Brian; Webber, Steven
Abstract: Condominium neighbourhoods are emerging in intensifying city centres as a response to market and demographic preferences for homeownership. While the multi-ownership structure of individual condominium buildings accommodates a short-term demand, the long-term implications for neighbourhoods is a source of concern. In particular, the presence of unit owners with varied acquisition objectives can lead to an anticommons problem resulting in building disinvestment due to an inability to reach decisions on sustainable maintenance fees and capital reserve funds, and a lack of end of lifecycle planning. The City of Toronto is experiencing unprecedented condominium development and serves as the basis for a case study that assesses the anticipated future neighbourhood challenges associated with a predominantly condominium-based form of ownership. Twenty-two local stakeholders were interviewed to identify problems that are viewed as sources of concern due to decisions made during the early stages of a building's lifecycle and the absence of a neighbourhood planning strategy. An analysis of the results indicates that lock-in, lacunae and neighbourhood effects will likely complicate revitalisation efforts as condominium neighbourhoods become more prevalent. Limited stakeholder recognition further suggests that it is necessary to raise a greater awareness of the potential anticommons impediments to long-term collective revitalisation actions. Highlights: Condominium neighbourhoods present long-term planning challenges that are currently poorly understood Range of stakeholder perspectives identify key lifecycle issues Results indicates that lock-in, lacunae and neighbourhood effects will likely complicate future neighbourhood revitalisation Need for greater awareness of the potential impediments to long-term collective revitalisation actions